2020
DOI: 10.3390/ijerph17186802
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Female Breast Cancer in the Middle East and North Africa

Abstract: Breast cancer, the most common cancer among women in the Middle East and North Africa (MENA) region, is associated with social and psychological implications deriving from women’s socio-cultural contexts. Examining 74 articles published between 2007 and 2019, this literature/narrative review explores the psychosocial aspects of female breast cancer in the MENA region. It highlights socio-cultural barriers to seeking help and socio-political factors influencing women’s experience with the disease. In 17 of 22 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 85 publications
(145 reference statements)
1
13
0
Order By: Relevance
“…The instability of emotions in light of the transitional stages—which women went through feeling like they were “dreaming,” starting with breast cancer diagnosis, receiving different methods of active treatment, and dealing with short and long treatment consequences—was a very significant finding in this study. This is also evident in other studies conducted in the Middle East that identified depression, anxiety, poor body image, and fear of cancer recurrence ( Fearon et al, 2020 ; Salem and Daher-Nashif, 2020 ). It is worthy to mention that what makes findings of this study unique is the fact that these Saudi women drifted away from perceiving the disease as a monster or an enemy once they started to describe a spiritual acceptance of this illness as their destiny, as Divine will, beyond their choice or control.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The instability of emotions in light of the transitional stages—which women went through feeling like they were “dreaming,” starting with breast cancer diagnosis, receiving different methods of active treatment, and dealing with short and long treatment consequences—was a very significant finding in this study. This is also evident in other studies conducted in the Middle East that identified depression, anxiety, poor body image, and fear of cancer recurrence ( Fearon et al, 2020 ; Salem and Daher-Nashif, 2020 ). It is worthy to mention that what makes findings of this study unique is the fact that these Saudi women drifted away from perceiving the disease as a monster or an enemy once they started to describe a spiritual acceptance of this illness as their destiny, as Divine will, beyond their choice or control.…”
Section: Discussionsupporting
confidence: 67%
“…Adding to those findings, the current study showed that some women expressed their frustration with the way that their closest relatives, including husbands and other family members, were treating and communicating with them. Some of the women expressed concerns regards their husband’s wishes to divorce or take a second wife ( Salem and Daher-Nashif, 2020 ). These concerns suggested that quality of life is influenced by marital relationships ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reporting on the psychosocial aspects of female breast cancer in the Middle East and Africa, Salem and Daher-Nashif argue that sociocultural factors such as religion and cultural values have a marked influence on BSE and BCS behaviors. They contend that there is a fissure between their beliefs that diagnosis of cancer can be perceived as “a punishment or test that only God can heal” and the belief that “one’s body is a gift from God and that it is ones’ responsibility to care for it” [ 26 ]. This contradiction is reflected in some Muslim women’s screening behavior in Qatar whereby those with fatalistic views may be less inclined to screen, ascribing a cancer diagnosis to God’s will, whereas the women that engage in BCS may regard it as a proactive means of caring for their body.…”
Section: Discussionmentioning
confidence: 99%
“…There is an assumption that Muslim women will be afraid or embarrassed of physical examination when attending a health facility. [28][29][30][31][32][33] In oPt more than 90% of the women are Muslim. Very few women in our study, however, reported feeling embarrassed or worried about the relationship with their husband as barriers to early presentation.…”
Section: Comparison To Findings Form Previous Researchmentioning
confidence: 99%